2021
DOI: 10.1016/j.aucc.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nurse-led sedation protocols on mechanically ventilated intensive care adults: A systematic review and meta-analysis

Abstract: Please cite this article as: Qi Z et al., Effects of nurse-led sedation protocols on mechanically ventilated intensive care adults: A systematic review and meta-analysis, Australian Critical Care,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Conversely, nurses are often involved in the titration of sedatives, analgesics, and vasopressors. As described above, previous studies have suggested that nurse-led sedation protocols lead to favorable outcomes [21]. From a patient-centered point of view, these contribute to optimal outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…Conversely, nurses are often involved in the titration of sedatives, analgesics, and vasopressors. As described above, previous studies have suggested that nurse-led sedation protocols lead to favorable outcomes [21]. From a patient-centered point of view, these contribute to optimal outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…For example, implementation of nurse-driven protocols has been associated with decreased mechanical ventilation days and ICU length of stay, 19 increased survival to hospital discharge after a resuscitation event, 20 and decreased ICU mortality. 21 These studies provide additional support for the positive outcomes associated with nursedriven protocols. Given the evidence supporting both the safety of peripherally infusing vasopressors and the benefits of nurse-driven protocols, a quality improvement project was developed to implement an evidence-based, nurse-driven protocol for the peripheral administration of vasopressors.…”
Section: Available Knowledgementioning
confidence: 83%
“…Nurse-driven protocols allow nurses to provide early interventions and have been shown to affect patient outcomes positively in many areas of critical care management. For example, implementation of nurse-driven protocols has been associated with decreased mechanical ventilation days and ICU length of stay, 19 increased survival to hospital discharge after a resuscitation event, 20 and decreased ICU mortality 21 . These studies provide additional support for the positive outcomes associated with nurse-driven protocols.…”
Section: Available Knowledgementioning
confidence: 87%
“…As described above, previous studies have suggested that nurse-led sedation protocols lead to favorable outcomes. [20] From a patient-centered point of view, these contribute to optimal outcomes. It is important to promote task-sharing, to reduce the burden on intensivists and improve the outcomes of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%